Dividend month premium in the Korean stock market - Bonha Koo; Joon Chae (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2020)
The dividend month premium is the phenomenon that firms have abnormal returns in predicted dividend month. This study aims to examine the dividend month premium in the Korean stock market, using common stocks listed on the KOSPI and KOSDAQ from January 1999 to December 2016. Abnormal returns are estimated using the following asset price models: capital asset pricing model, Fama-French three-factor model and the Fama-French-Carhart four-factor model. This study finds positive abnormal returns in predicted dividend months, and even for the within-firm portfolio that buys stocks in the predicted dividend months and sells the same stocks in other months. The price impact and the subsequent reversals are greater with lower liquidity and higher dividend yield, implying that the price pressure from dividend-seeking investors affects this dividend month premium. In addition, the anomalies with the pre-declaration stock are smaller than the post-declaration stock, suggesting the necessity to improve the cash dividend policy of postdeclaration for market efficiency.
Keywords: 330; Market efficiency; Dividend; Dividend month premium; Price pressure